2010
DOI: 10.1111/j.1365-2702.2009.02966.x
|View full text |Cite
|
Sign up to set email alerts
|

Lived experience of epilepsy from the perspective of children in Taiwan

Abstract: Public health and school nurses can apply our findings to educate school teachers and parents about epilepsy and encourage activities that allow children with and without epilepsy to interact, thus improving peer relationships and reducing stigmatisation. Children with and without epilepsy would also benefit from an age-appropriate education manual that includes causes of epilepsy, treatment, dealing with seizures and psychological and social adaptation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
(79 reference statements)
0
23
0
Order By: Relevance
“…Participants were "afraid to die" 16 and this was expressed particularly among adolescents who lived alone or had a limited support network. However, some participants indicated that they would prefer to die during a seizure than live a "life ruined by" 38 brain damage.…”
Section: Tablementioning
confidence: 99%
See 4 more Smart Citations
“…Participants were "afraid to die" 16 and this was expressed particularly among adolescents who lived alone or had a limited support network. However, some participants indicated that they would prefer to die during a seizure than live a "life ruined by" 38 brain damage.…”
Section: Tablementioning
confidence: 99%
“…16 This perceived intellectual inferiority was discouraging, and some participants believed that their "schooling had gone to waste." 12 Participants also missed school due to hospital admissions or doctor appointments.…”
Section: Inability To Achieve Academicallymentioning
confidence: 99%
See 3 more Smart Citations